Quantitatively describing the downstream effects of an abrupt land cover transition: buffering effects of a forest remnant on a stream impacted by cattle grazing. Issue 3 (3rd July 2018) - Feijó-Lima, Rafael; Mcleay, Scott M.; Silva-Junior, Eduardo F.; Tromboni, Flavia; Moulton, Timothy P.; Zandonà, Eugenia; Thomas, Steven A.
ABSTRACT: Human activities often produce highly fragmented watersheds with respect to the distribution of vegetation, and this condition can extend from the watershed boundary to the riparian corridor. Because streams are transport-dominated ecosystems, it is unlikely that changes in instream conditions map synchronously with the spatial pattern of riparian fragmentation. Riparian influences are likely to be propagated some distance downstream, creating a downstream "shadow" of upstream riparian conditions. To investigate the distance over which upstream riparian effects can still be detected, we sampled 15 sites along 1050 m of a headwater stream incorporating an abrupt transition. We measured a suite of benthic invertebrate metrics as well as physicochemical and environmental variables. We employed a threshold modeling approach to examine whether variables were displaced significantly downstream as our stream traversed the riparian discontinuity. Alternative nonlinear models were tested and inverse estimation was applied to estimate the distance over which the variables started to shift from upstream stable conditions and how far the buffering effects of the upstream forest could be detected. While some variables such as substrate particle size metrics and the proportion of filterers in the community transitioned upstream from the riparian boundary, we observed a sharp increase in periphyton chlorophyll a concentrations starting 130 m below the canopy cover transition. A decrease in fine sediment size started 386 m below the transition. Invertebrate abundances and family richness decreased along the transition while the proportion of functional feeding groups showed a shift from a dominance of collector-gatherers to a dominance of scraper-grazers, mainly driven by the responses of chironomids and leptohyphid ephemeropterans. Overall, the riparian transition effects on the invertebrate community seemed to be primarily driven by substrate composition and secondly by the shift in resource availability. Non-metric multidimensional scaling analysis revealed that the whole community was still changing at the downstream-most station of the sampled reach. Our methodological approach allowed us to better visualize the synergistic effects of food resource availability and substrate size in locally impacted invertebrate communities along a manmade transition.